2015
DOI: 10.1253/circj.cj-15-0113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemodialysis on 7-Year Clinical Outcomes After Sirolimus-Eluting Stent Implantation

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jpThe sirolimus-eluting stent (SES [Cypher, Cordis/Johnson & Johnson, Miami, FL, USA]), one of the most widely used first-generation drug-eluting stents (DES), significantly reduced the rate of target lesion revascularization (TLR) compared with BMS implants in randomized control trials. 4-7 However, all the well-designed studies of DES have excluded HD patients in order to avoid clinical heterogeneity of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Dialysis is a wellknown predictor for MACE after coronary stenting. 2,8, 25 Although only 4.9% of the patients were on dialysis, dialysis was the strongest predictor for MACE in the present study ( Figure S1). Whereas clinically driven TLR rate was 2.5% at 1 year and 3.7% at 3 years in non-dialysis patients, it was 13.1% at 1 year and 18.4% at 3 years in dialysis patients.…”
Section: Predictors Of Macementioning
confidence: 59%
“…Dialysis is a wellknown predictor for MACE after coronary stenting. 2,8, 25 Although only 4.9% of the patients were on dialysis, dialysis was the strongest predictor for MACE in the present study ( Figure S1). Whereas clinically driven TLR rate was 2.5% at 1 year and 3.7% at 3 years in non-dialysis patients, it was 13.1% at 1 year and 18.4% at 3 years in dialysis patients.…”
Section: Predictors Of Macementioning
confidence: 59%
“…In terms of HD patients undergoing percutaneous coronary intervention, several reports have already revealed that HD patients have a poorer prognosis than non-HD patients. 11,12 However, only a few studies to date have examined the clinical outcomes in HD patients with CLI who undergo EVT, and compared the prognosis as well as its predictors between HD and non-HD patients. 13,14 In addition, causes of death in HD patients after EVT for CLI are not clarified in detail, although cardiovascular death is believed to be the leading cause.…”
mentioning
confidence: 99%
“…The reasons for this are considered to be multifactorial. First, dialysis patients tend to have more advanced comorbidities including hypertension, diabetes mellitus, peripheral artery disease, and heart failure than nondialysis patients . These underlying diseases, especially heart failure in this study, may be associated with inā€hospital adverse outcomes in dialysis patients undergoing PCI.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have reported that dialysis patients have an increased risk of adverse outcomes during and after PCI compared with nondialysis patients . However, details on the characteristics and outcomes after PCI in dialysis patients remain unclear because the sample size of this group of patients is limited .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation